Las relaciones de los órganos del poder político en el nuevo contexto político mexicano - Prado Maillard, José Luis (2023)
The declining of the hegemonic presidential rule that Mexico knew in their institutions for 71 years was slow but effective. It is a gradual evolution that gives time to the power and to their opponents to adapt their selves to the critic. They knew to critic and to be critiqued peacefully. Progressively, the Mexican political system transforms since hegemonic to plural, keeping in this way one important element of the democracy before the posterior alternation in the political power organs.